A diffusion process with a self-similar random potential with two exponents, III. Issue 3 (4th May 2021) - Suzuki, Yuki
Abstract: We consider a new class of one-dimensional diffusion processes with self-similar random potentials. The self-similar random potential has different exponents to the left and the right hand sides of the origin. We show that, because of the difference between the two exponents, the long-time behaviors of our process on the left and the right hand sides of the origin are quite different from each other.